2022
DOI: 10.3389/fmolb.2022.876780
|View full text |Cite
|
Sign up to set email alerts
|

Interlaboratory Studies Using the NISTmAb to Advance Biopharmaceutical Structural Analytics

Abstract: Biopharmaceuticals such as monoclonal antibodies are required to be rigorously characterized using a wide range of analytical methods. Various material properties must be characterized and well controlled to assure that clinically relevant features and critical quality attributes are maintained. A thorough understanding of analytical method performance metrics, particularly emerging methods designed to address measurement gaps, is required to assure methods are appropriate for their intended use in assuring dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
1
3
0
Order By: Relevance
“…The CCSD analysis ( Figure 2 ) also indicated that batch-to-batch variability was small, as the average CCSD value was 5.2 ± 2.5 ppb at T0. Our CCSD analysis is consistent with the NMR data already reported on monoclonal antibodies to assess their higher order structures [ 10 , 17 ].…”
Section: Resultssupporting
confidence: 89%
“…The CCSD analysis ( Figure 2 ) also indicated that batch-to-batch variability was small, as the average CCSD value was 5.2 ± 2.5 ppb at T0. Our CCSD analysis is consistent with the NMR data already reported on monoclonal antibodies to assess their higher order structures [ 10 , 17 ].…”
Section: Resultssupporting
confidence: 89%
“…Except for in-source generated glycopeptides, the findings on NISTmAb glycosylation interlaboratory studies 45,46 on released N-glycans are consistent, with the relative GADS and FLD glycoform abundances of G4H3F, G4H4F, and G4H5F accounting for 85% of the total (Figures 2−4). GADS values seem to provide reasonable estimates of the relative concentrations at the protein level.…”
Section: Fluorescence and Ms Quantification Of Mabsmentioning
confidence: 60%
“…In other words, alterations in backbone amide hydrogen chemical environment such as changes in hydrogen bonding and/or solvent accessibility result in measurable changes in HDX rates. Applications for continuous labeling HDX‐MS are far reaching in both academic and industry settings and have been used to map protein‐protein interactions (PPIs) or protein interactions with cognate ligand, small molecules, nucleic acids, and antibodies [27–30] …”
Section: Hydrogen Deuterium Exchange Mass Spectrometrymentioning
confidence: 99%
“…Applications for continuous labeling HDX-MS are far reaching in both academic and industry settings and have been used to map protein-protein interactions (PPIs) or protein interactions with cognate ligand, small molecules, nucleic acids, and antibodies. [27][28][29][30] Alternatively, HDX-MS experiments can also utilize a pulsed labeling approach (Figure 2C -pulsed labeling). [31] In this workflow protein samples are first perturbed for different time intervals and then subjected to a single, short deuterium labeling step.…”
Section: Mechanism Of Exchange and Experimental Approachmentioning
confidence: 99%